PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) UNTUK MENGURANGI PENGEMBALIAN PEKERJAAN (JOB RETURN) SEBAGAI USAHA DALAM MEMENUHI KEPUASAN PELANGGAN (Studi pada Pelanggan CV. AHASS Sahabat Sejati Motor di Kota Semarang) - Islami, Kharisma; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2017)
This study motivated the incosistency of previous study on total quality management on customer satisfaction which is characterized by reduction of job return that where there are research gaps. This study aims to examine the total quality management which include focus on the customer, obsession of quality, team work, engangement and empowerment on customer satisfaction.The population in this study are all customer in CV. AHASS Sahabat Sejati Motor in Semarang. Data collection method used is the method of sampling the sample amount to 110 respondents. The analytical method used is multiple regression.Based on statistical data analysis, the indicators in this study are valid and reliable. The greatest variable is the variable of focus on the customer was 0,852, whereas the smallest variable is the variable of team work was 0,001. The result of the study found that all of the independent variables and a significant positive effect on the dependent variable.